Eksaserbasi Asma Berat akibat Pneumonia Komunitas pada Anak dengan Predisposisi Atopik: Sebuah Laporan Kasus - Zheva Aprillia Yozevi; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Asthma is a chronic inflammatory airway disease prone to exacerbations triggered by various factors, notably infections. Community-acquired pneumonia (CAP) can exacerbate airway inflammation and trigger severe asthma exacerbations in children. This report discusses a 7-year-and-1-month-old girl presenting with shortness of breath that worsened 7 hours prior to admission, accompanied by wheezing, restlessness, and limited speech. The complaints were preceded by a 3-day cough and a 2-day runny nose. The patient had a history of asthma since age 3, personal atopy, and maternal asthma. Physical examination revealed tachypnea, tachycardia, oxygen saturation of 89% on room air, intercostal retractions, nasal flaring, and bilateral expiratory wheezing. Laboratory findings indicated neutrophilic leukocytosis, eosinophilia (12%), and an increased erythrocyte sedimentation rate (59 mm/hour). Chest radiograph showed right suprahilar consolidation and bilateral paracardial infiltrates, suggestive of right lobe pneumonia and left lung bronchopneumonia. The patient was diagnosed with severe asthma exacerbation on partially controlled mild persistent asthma, accompanied by community-acquired pneumonia. Management included oxygen therapy, inhaled bronchedilators, intravenous antibiotics and aminophylline, and supportive therapy. Evaluation demonstrated clinical improvement characterized by increased oxygen saturation, decreased respiratory rate, and reduced respiratory distress. This case emphasizes that CAP can act as a major trigger for severe asthma exacerbations in children with an atopic predisposition, making early diagnosis and comprehensive management crucial to improve clinical outcomes.